Association of Helicobacter pylori Infection with Severity and Clinical Presentation of Gastric Ulcer: A Cross-Sectional Clinical Study - Sumreen, Muhammad Daud, Sham Lal Prithiani, Sheema Khan, Nadeem Sharif, Ifrah Zafar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Helicobacter pylori infection is a major etiological factor in gastric ulcer disease and is associated with variations in symptom severity and ulcer morphology. Understanding this relationship is essential in regions with high infection prevalence such as Pakistan. Objective: To determine the association between H. pylori infection and the clinical severity and presentation of gastric ulcer among patients undergoing upper gastrointestinal endoscopy. Methods: A cross-sectional study was conducted at SMBBMC Lyari, Karachi, and RMI Peshawar from June 2022 to May 2023. A total of 100 patients with endoscopically confirmed gastric ulcer were enrolled. Clinical symptoms, endoscopic findings, and ulcer severity scores were compared between H. pylori–positive and –negative groups. Infection was confirmed using rapid urease test and histopathology. Data were analyzed using SPSS 25, with p < 0.05 considered significant. Results: H. pylori infection was present in 62% of patients. Infected individuals exhibited more severe epigastric pain, higher frequencies of nausea, early satiety, and significant weight loss. Endoscopic evaluation showed that H. pylori–positive patients had larger ulcers (1.89 ± 0.61 cm vs. 1.43 ± 0.52 cm), more deep lesions, increased ulcer multiplicity, and a higher rate of active bleeding. The mean ulcer severity score was significantly greater in the infected group (6.7 ± 1.8 vs. 5.0 ± 1.5; p < 0.001). Logistic regression confirmed H. pylori infection as an independent predictor of severe ulcer disease. Conclusion: H. pylori infection is strongly associated with increased severity and more pronounced clinical and endoscopic features of gastric ulcer. Routine detection and timely eradication therapy are crucial to reducing symptom burden, complications, and recurrence. Keywords: Helicobacter pylori, gastric ulcer, endoscopy, ulcer severity, clinical presentation.